Comprehensive and safe school strategy during COVID-19 pandemic - Susanna Esposito; Nicola Cotugno; Nicola Principi (BMC, 2021)
Abstract Background Although several studies have tried to evaluate the real efficacy of school closure for pandemic control over time, no definitive answer to this question has been given. Moreover, it has not been clarified whether children or teenagers could be considered a problem for SARS-CoV-2 diffusion or, on the contrary, whether parents and school workers play a greater role. The aims of this review are to discuss about children's safety at school and the better strategies currently able to reduce the risk of SARS-CoV-2 infection at school. Main aim Compared to adults, very few cases of COVID-19 were diagnosed in children, who generally suffered from an asymptomatic infection or a mild disease. Moreover, school closure is systematically associated with the development of problems involving students, teachers and parents, particularly among populations with poor resources. Although several researches have tried to evaluate the real efficacy of school closure for pandemic control over time, no definitive answer to this question has been given. Available findings seem to confirm that to ensure adequate learning and to avoid social and economic problems, schools must remain open, provided that the adults who follow children at home and at school absolutely comply with recommendations for prevention measures and that school facilities can be optimized in order to significantly reduce the spread of infection. In this regard, the universal use of face masks in addition to hand hygiene and safe distancing in schools, at least starting from the age of 6 years, seems extremely useful. Moreover, since the beginning of the COVID-19 outbreak the use of telemedicine to manage suspected SARS-CoV-2-infected individuals in the community has appeared to be an easy and effective measure to solve many paediatric problems and could represent a further support to schools . Conclusions We think that schools must remain open, despite COVID-19 pandemic. However, several problems strictly related to school frequency and reduction of infectious risk must be solved before school attendance can be considered completely safe. A single more in-depth guideline agreed between countries with the same school problems could be very useful in eliminating doubts and fostering the compliance of students, teachers and non-teaching school staff reducing errors and misinterpretations.